Humanism : a very short introduction - Law, Stephen (Oxford : Oxford University Press, 2011)
Philosopher Stephen Law explains why humanism--though a rejection of religion--nevertheless provides both a moral basis and a meaning for our lives.-publisher description.
History of humanism -- Arguments for the existence of God -- An argument against the existence of God -- Humanism and morality -- Humanism and secularism -- Humanism and moral and religious education -- The meaning of life -- Humanist ceremonies.
Includes bibliographical references (p. 143-146) and index.
Keywords: Humanism